2022
DOI: 10.1017/jfm.2022.385
|View full text |Cite
|
Sign up to set email alerts
|

Transition boundaries and an order-to-chaos map for the flow field past a flapping foil

Abstract: The present study focuses on identifying dynamical transition boundaries and presents an order-to-chaos map for the unsteady flow field of a flapping foil in the low Reynolds number regime. The effect of an extensive parametric space, covering a large number of kinematic conditions, has been investigated. It is shown that the conventional non-dimensional parameters cannot effectively capture the changes in the flow field due to the variations in the relevant kinematic parameters and are unable to demarcate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
(90 reference statements)
0
13
0
Order By: Relevance
“…Majumdar et al ( 9 ), for a plunging configuration, reported quasi-periodicity around 1.65 and chaos at 1.9 . For actuated pitching–plunging, Bose et al ( 4 ) also reported a similar range: a quasi-periodic flow-field at 1.6 , appearance of intermittency at 1.66 , and sustained chaos at 2.5 ; note that the reporting of Bose et al ( 4 ) was for zero phase difference between pitch and plunge motions, a non-zero phase-gap would have changed these onsets ( 10 ). On the other hand, as seen in the present results, aperiodic transition is completely absent (or delayed) due to passive pitch dynamics even at as high as 3.0 ; see Fig.…”
Section: Dynamical Behavior Of Ap–pp and Ap–ap Systemsmentioning
confidence: 85%
See 3 more Smart Citations
“…Majumdar et al ( 9 ), for a plunging configuration, reported quasi-periodicity around 1.65 and chaos at 1.9 . For actuated pitching–plunging, Bose et al ( 4 ) also reported a similar range: a quasi-periodic flow-field at 1.6 , appearance of intermittency at 1.66 , and sustained chaos at 2.5 ; note that the reporting of Bose et al ( 4 ) was for zero phase difference between pitch and plunge motions, a non-zero phase-gap would have changed these onsets ( 10 ). On the other hand, as seen in the present results, aperiodic transition is completely absent (or delayed) due to passive pitch dynamics even at as high as 3.0 ; see Fig.…”
Section: Dynamical Behavior Of Ap–pp and Ap–ap Systemsmentioning
confidence: 85%
“…2 C and F)]. The primary LEV for the AP–AP foil was also stronger (the circulation values should be noted in the figure), which approached the regime of aperiodicity ( 10 ). Furthermore, the shedding of a secondary vortex along with the main TEV contributed towards the loss of periodicity and influenced the aerodynamic loads; see supplementary Video SV2 .…”
Section: Dynamical Behavior Of Ap–pp and Ap–ap Systemsmentioning
confidence: 89%
See 2 more Smart Citations
“…The wake transition behind rigid flapping foils has been studied comprehensively in the recent literature for different kinematics, such as pure heaving (Lai & Platzer 1999; Lewin & Haj-Hariri 2003; Ashraf, Young & Lai 2012; Badrinath, Bose & Sarkar 2017; Majumdar, Bose & Sarkar 2020 a , b ) and pure pitching (Koochesfahani 1989; Godoy-Diana, Aider & Wesfreid 2008; Schnipper, Andersen & Bohr 2009; Shinde & Arakeri 2013), as well as simultaneous heaving–pitching (Lentink et al. 2010; Bose & Sarkar 2018; Bose, Gupta & Sarkar 2021; Majumdar, Bose & Sarkar 2022). The dynamic plunge velocity () or Strouhal number () was used as the control parameter to study the transition; here, , where and are the plunge/heave amplitude and frequency, respectively; is the non-dimensional heave amplitude; and is the reduced frequency, with being the chord length of the foil.…”
Section: Introductionmentioning
confidence: 99%